Methodology of determining the investment attraction of the region (Journal of Economic Research & Business Administration, 2018)
The necessity of socio-economic development and investment attractiveness of the regions is shown.The urgency of an assessment and forecasting of investment attractiveness of the region, for advancingformation of budgetary and off-budget part of investment expenses is revealed. The novelty of the researchconsists in the systematization of retrospective and statistical data, modeling the impact of socioeconomicdevelopment indicators on the volume of the gross regional product. Methods of theoreticaland empirical research, as well as methods of mathematical modeling were applied. The analysis of existingtheoretical studies on the investment attractiveness of the region and its components. It is shown thatthe investment attractiveness should be defined as an economic category, allowing a potential investor to make judgment on the combination of regional factors and to determine the capabilities and limitationsof the implementation of the investment interests in the investment of capital into the region in thepresent and future periods. The necessity of the model of indirect estimation of investment attractivenessallowing to plan investment activity and to raise the level of social and economic development of the regionis revealed. Indicators of socio-economic development for the regression analysis were determined.The method of estimation of investment attractiveness of regions is offered, developed with applicationof provisions of the theory of systems, namely the principles of necessary variety of elements, minimumsufficiency and their target orientation which in turn is very valuable for the potential investor.